(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Breast cancer (BC) is the most common cancer in women worldwide. Letrozole (LTZ) is a third-generation selective nonsteroidal aromatase inhibitor and one of many anticancer drugs. Conventional LTZ therapies for BC are often administered orally or parenterally and frequently result in severe systemic side effects. To improve this situation, efforts have been made for an advanced drug delivery system that accurately releases the drug at the target site and increases therapeutic efficacy with minimal side effects. Here, we report the delivery system based on poloxomer 188 as a platform for LTZ-based solid lipid nanoparticles (SLNs) in cancer cells. The particle size, PDI, ZP, and DEE % of optimally selected LTZ -SLNs (pH 7.4) were 82.16 ± 7.24 nm, 0.287 ± 0.05, -15.0 ± 8.83 mV, and 57.89 ± 1.22 %, respectively. The SEM of LTZ -SLNs shows hexagonal phase stacking with a nanoflock morphology. The TEM image clearly shows that the introduced LTZ -SLN drugs contain LTZ drugs inside the particles. After 48 hours, it was reported that the percentage of LTZ release was 82.34%. LTZ-SLNs showed significant cytotoxic properties with an IC50 of 2.22ug/ml. The results of histopatholgical study confirmed that LTZ-SLNs can minimize the cytotoxicity of LTZ. Overall, the prepared nanoformulation offers great potential for BC treatment.